Seeking For Pleasure: The Risk Factor Between Voluntary Client Versus Involuntary Client - Amin Al Haadi Shafie; Mizan Adiliah Ahmad Ibrahim; Nurhafizah Mohd. Sukor; Mohd Khairul Anuar Rahimi; Nur Faizah Abdul Kahar (Center for Promoting Ideas (CPI), USA, 2024)
Indexed by ERA